Biochemical Analysis of Antioxidant System Enzymes in Type 2 Diabetes - Abdurashidovich, Abdurashidov Asilbek; qizi, Elmurodova Sarvinoz G'ulomjon; D. U., Mamadiyarova (American Journal of Biomedicine and Pharmacy, 2025)
The study of lipid peroxidation (LPO) processes has been studied in depth since the late 1970s. In the works of a number of authors, it has been shown that in patients with experimental diabetes and diabetes mellitus, the level of lipid peroxidation products in blood plasma increases and the activity of antioxidant defense enzymes decreases. It is known that the induction of lipid peroxidation in biological membranes can be carried out by anion radicals and other active forms of oxygen, which triggers a whole cascade of free radical oxidation reactions, the products of which have a toxic effect on the cell and may be one of the pathogenetic factors of the specific development of insulin-dependent diabetes mellitus. Since the primary and secondary products of lipid peroxidation have a detrimental effect on the cell, the body has regulatory mechanisms that limit the accumulation of highly toxic products, which is called antioxidant defense. Enzymes such as superoxide dismutase (SOD), catalase, glutathione peroxidase (GLP), and glutathione reductase play a leading role in the regulation of lipid peroxidation. There are conflicting opinions in the literature about the nature of changes in the activity of antioxidant enzymes in diabetes mellitus in children. Therefore, the aim of our study was to show how the activity of antioxidant enzymes in children changes depending on the degree of compensation and duration of the disease.